Effect of interest rate on bank deposits: Evidences from Islamic and non-Islamic economies - Saba Mushtaq; Danish Ahmed Siddiqui (Future Business Journal, 2017)
Banking sector is the backbone of any country׳s economy and bank deposits are the major tool of success for banking sector. Bank deposits are also a major part and determinant of country׳s saving. According to economic theories and practical considerations, interest rate is considered one of the major elements that can affect savings as well as bank deposits. But as we knows that in Islam interest is considered forbidden and Muslims tries to avoid interest income , So the basic purpose of this study is to know the fact that either religious factors have any effect on Muslim's decision while keeping their saving in banks. We used panel ARDL(Autoregressive Distributed Lag) method by using 23 non-Islamic and 23 Islamic countries data from 1999 to 2014 for this study. Results showed that in Islamic countries interest rate don't have any impact on bank deposits both in long run and short run. But in the case of non-Islamic countries interest rate have positive significant impact on bank deposits. Hence there is need of Islamic banks in countries with more Muslim population and there should be different economic policies for Islamic countries as religious factor affects decision of Muslims and interest rate doesn't have any impact on bank׳s deposits.
Keywords: 650; Bank deposits; Interest rate; Islamic; Panel data